Utilizing Tiktok In Project-Based Learning At Intermediate English-Speaking Class: Pemanfaatan Tiktok Sebagai Alat Bantu Dalam Penggunaan Metode Pembelajaran Berbasis Proyek Pada Kelas Intermediate English Speaking - Christina Wulandari Suripto; Indra Perdana; Maria Arina Luardini (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Intermediate English Speaking expected the students to be able to use vocabulary that is relevant to the material and fully participated in casual conversation including describing an object. In the 21st century, critical thinking, problem-solving, communication, and collaboration or 4Cs skills should be mastered by students. So, the lecturer uses Project Based Learning as the method suggested by the government, together with TikTok, the popular application among the students, which can facilitate them to achieve their goals. This paper will present the implementation of Project Based Learning in the Intermediate English Speaking class of English Department, FKIP, Palangka Raya University, and the utilization of the TikTok application as the tool for creating the project. This paper also describes the improvement of students’ speaking abilities in their video projects. The implementation of PBL in the Intermediate English Speaking classroom by utilizing TikTok is a great combination in increasing students speaking ability.